An investigation into the teachers’ attitudes towards the performance of the girl child in upper primary grades in Gokwe South District. - Chikara, Owen (Midlands State University, 2017)
The research was set up to investigate teacher’s attitudes towards the performance of girls in upper primary grades in Gokwe South District in the Midlands province of Zimbabwe. The research was as a result of seeing the plight of many girls who are performing poorly in academics. The poor performance of girls affect their secondary enrolment and also affect their opportunity in the job market. The research design employed was the descriptive survey and this was because of its ability to address the current issues during the time of study. The research findings were that, teachers generally linked pupils’ academic performance to gender. Teachers believed that boys perform better than girls in upper primary schools which shows that teachers have negative attitudes towards girls. Those who had positive attitudes to girl’s performance were as a result of teachers’ in-service and some attributed this to experience. The conclusions that the researcher drew were that there was need for schools to sensitive on gender balance. There is need of awareness campaigns in schools about girl child’s education.